Tetraacylgermanes as highly efficient photoinitiators for visible light cured dimethacrylate resins and dental composites. Issue 15 (18th December 2017) - Moszner, Norbert; Fischer, Urs Karl; Lamparth, Iris; Fässler, Pascal; Radebner, Judith; Eibel, Anna; Haas, Michael; Gescheidt, Georg; Stueger, Harald
ABSTRACT: Tetrabenzoylgermane1 and various substituted tetrabenzoylgermanes2 –7 were investigated as visible light (VL) photoinitiators (PIs) for dental dimethacrylate resins and dimethacrylate‐based composites. The tetrabenzoylgermanes1 –7 show a very strong VL absorption between 400 and 450 nm. Substituents on the benzoyl chromophore strongly influence their properties such as melting point, solubility, absorption behavior, or PI reactivity. A good photobleaching behavior and a very high reactivity as VL PI was found in photo‐differential scanning calorimeter experiments for selected tetrabenzoylgermanes. Composite pastes containing only ∼0.1 wt % of Ge‐PI exhibited a sufficient photocuring due to the high PI‐reactivity of the tetraacylgermanes. Among the investigated germane PIs, tetrakis(2‐methylbenzoyl)germane2 shows the best performance as VL PI for restorative composites and enables the composites to be photocured using an LED with an emission maximum of 500 nm. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46115. Abstract :